2017
DOI: 10.1093/scipol/scx016
|View full text |Cite
|
Sign up to set email alerts
|

Advisory commissions, academic expertise and democratic legitimacy: the case of Norway

Abstract: Commissions appointed to examine and propose solutions to major policy problems play a vital role in policy formulation in the Nordic countries. Whereas existing accounts emphasize the corporatist and statist features of these bodies, this article investigates the changing role of academic knowledge within commissions. It does so through an empirical and normative analysis of Norwegian ad hoc advisory commissions appointed during the period 1967-2013. Based on a quantitative analysis of commission composition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 85 publications
(64 citation statements)
references
References 26 publications
2
61
0
1
Order By: Relevance
“…The reports are written by ad hoc advisory commissions appointed by the government to examine major policy issues and to suggest possible solutions for policymaking. Both experts and laypeople participate in these commissions 54. The reports have an important role in the formulation of Norwegian public policy and serve the need to back up political proposals with references to research and to integrate interest groups in the policy process.…”
Section: Methodsmentioning
confidence: 99%
“…The reports are written by ad hoc advisory commissions appointed by the government to examine major policy issues and to suggest possible solutions for policymaking. Both experts and laypeople participate in these commissions 54. The reports have an important role in the formulation of Norwegian public policy and serve the need to back up political proposals with references to research and to integrate interest groups in the policy process.…”
Section: Methodsmentioning
confidence: 99%
“…Their prevalence has triggered a new research field within public administration studies, which has traced the rise of these institutions not only on the EU level, but also within nation states (see e.g. Busuioc, 2013;Christensen & Holst 2017;Curtin 2007Curtin , 2017Egeberg, Schaefer & Trondal, 2003;Egeberg & Trondal, 2011;Ennser-Jedenastik, 2015;Gornitzka & Krick, 2018;Kelemen, 2002;Lord, 2011). Recently, research on these institutions has directed more attention to the social and political ties of expert bodies (Busuioc, 2013;Ennser-Jedenastik, 2016;Gornitzka & Krick, 2018;Lodge, 2008;Pérez-Durán, 2017), i.e.…”
Section: Introductionmentioning
confidence: 99%
“…In terms of the differences, the Danish SCACJ additionally included a legal scholar and a ministry representative, while the Norwegian Commission included one representative from an NGO who is well known in Norway for advocating for increased procedural rights for complainants and their next of kin. Nordic ad hoc commissions have traditionally been characterised by broad interest representation, although a recent analysis has shown that academics increasingly make up a substantial proportion of commission members (Christensen & Holst, 2017). In this case, however, there was not much difference between the member composition of the Danish SCACJ and the Norwegian Commission, which indicates that criminal procedural law in these countries is largely understood to be the domain of expert legal practitioners in the criminal justice system, with only minimal, if any, representation from extra-legal stakeholders.…”
Section: Backgrounds To Norwegian/danish Legal Policy Proceduresmentioning
confidence: 99%